Species of the genus Thrips (Thysanoptera) from Peninsular Malaysia, with a checklist of recorded Thripidae - Mound, L. A.; Azidah, A. A. (Zootaxa, 2009)
An illustrated key is provided to 23 species of the genus Thrips from Peninsular Malaysia, including one new species and seven species not previously recorded from this country. Most of the specimens came from a recent survey of crop plants, and this survey produced several interesting species of other genera of Thripidae. The invasive pest species, Frankliniella occidentalis and Frankliniella intonsa, were abundant in highland areas, and an African species not previously known from Asia, Ceratothripoides brunneus, was found commonly particularly in lowland areas. A checklist is provided of 78 species of Thripidae recorded from Peninsular Malaysia.